Kesesuaian Jenis Tanaman Pertanian dengan Kualitas Air Irigasi dari Beberapa Mata Air Karst di Kabupaten Tuban - Hari Siswoyo; Mohammad Bisri; Mohammad Taufiq; Vanadani Pranantya (Universitas Trunojoyo Madura, 2020)
This research was conducted with the aim to describe the types of non-paddy agricultural crops that can be cultivated on agricultural land with irrigation water sources from karst springs. This research was conducted at 10 locations of karst springs that are used to irrigate agricultural land in Tuban Regency. Determination of alternative of types of non-rice agricultural crops is done by integrating the irrigation water quality index model, criteria of relative tolerance of crops to salt, and criteria of non-rice agricultural crops that have high economic value. Irrigation water quality index values from karst springs at the study location ranged from 73.99 to 76.23, which is in the range of 70-85 with a low water use restriction. Based on the irrigation water quality index values it can be recommended that water supply for irrigation from karst springs is not carried out on salt sensitive crops. The non-paddy agricultural crop types that can be recommended to be planted in the study location are corn (Zea mays), soybeans (Glycine max), peanuts (Arachis hypogaea), sweet potatoes (Ipomoea batatas), tomatoes (Lycopersicon lycopersicum), eggplants (Solanum melongena), cucumbers (Cucumis sativus), spinach (Spinacia oleracea), melons (Cucumis melo), and watermelons (Citrullus lanatus).